Dietary Omega 3 Polyunsaturated Fatty Acids and Alzheimer's Disease: Interaction with Apolipoprotein E Genotype - Barberger-Gateau, P.; Samieri, C.; Feart, C.; Plourde, M. (Current Alzheimer Research, 2011)
Epidemiological studies suggest a protective role of omega-3 poly-unsaturated fatty acids (n-3 PUFA) against Alzheimer's disease (AD). However, most intervention studies of supplementation with n-3 PUFA have yielded disappointing results. One reason for such discordant results may result from inadequate targeting of individuals who might benefit from the supplementation, in particular because of their genetic susceptibility to AD. The ε4 allele of the apolipoprotein E gene (ApoE) is a genetic risk factor for late-onset AD. ApoE plays a key role in the transport of cholesterol and other lipids involved in brain composition and functioning. The action of n-3 PUFA on the aging brain might therefore differ according to ApoE polymorphism. The aim of this review is to examine the interaction between dietary fatty acids and ApoE genotype on the risk for AD. Carriers of the ε4 allele tend to be the most responsive to changes in dietary fat and cholesterol. Conversely, several epidemiological studies suggest a protective effect of long-chain n-3 PUFA on cognitive decline only in those who do not carry the ε4 but with inconsistent results. An intervention study showed that only non-carriers had increased concentrations of long-chain n-3 PUFA in response to supplementation. The mechanisms underlying this gene-by-diet interaction on AD risk may involve impaired fatty acids and cholesterol transport, altered metabolism of n-3 PUFA, glucose or ketones, or modification of other risk factors of AD in ε4 carriers. Further research is needed to explain the differential effect of n-3 PUFA on AD according to ApoE genotype
Keywords: ApoE polymorphism